An investigation on the types of humour in English language teaching among Malaysian lecturers in higher education - Mazlin Binti Mohamed Mokhtar, Intan Safinas Mohd Ariff Albakri, Mohd Haniff Mohd Tahir, Puteri Zarina Megat Khalid, Khazaila Zaini (Tanjung Malim, 2024)
An investigation on the types of humour in English language teaching among Malaysian lecturers in higher education by Mazlin Binti Mohamed Mokhtar, Intan Safinas Mohd Ariff Albakri, Mohd Haniff Mohd Tahir, Puteri Zarina Megat Khalid, Khazaila Zaini